BAHASA, BIAS GENDER DAN IDENTITASNYA PADA BUKU AL-ARABIYAH LIL INDUNIYSIYYIN - Aldzakhiroh, Nilna; Nopriansyah, Beri; Nasution, Annisa Hasanah; Fikri, Shofil (STIQ Amuntai, 2024)
Learning Arabic is a complex process that not only involves linguistic aspects, but in the context of learning Arabic, it also requires important aspects, such as the relationship between language, gender bias, and identity. Language is important because it functions as a means of communication for people in their daily lives, so learning Arabic is closely related to gender bias and language identity. This research aims to explain language, gender bias, and identity in the book Al-Arobiyyah lil Induniysiyyin. This type of research is qualitative and uses a library research approach by obtaining data from journals, books, and other sources relevant to the research. The results of this research reveal that the function of language, apart from being a means of communication, also includes self-expression, identity, and culture, as well as education and learning. An important aspect of learning Arabic is gender bias. Forms of gender bias in the book Al-Arobiyyah lil Induniysiyyin include the role of men being more dominant in terms of work, nature, and role in Arabic texts compared to the role of women. Forms of gender bias are divided into three categories: mudzakar (masculine), muanats (feminine), and functional (neutral). Apart from gender bias, another aspect is language identity. The forms of language and identity learned in Arabic can be summarized as religious identity, cultural identity, and national identity.